Marketing channels for food procurement during the COVID-19 pandemic in Brazil. (Polis (Santiago), 2022)
This paper analyzes food buying practices and market places during the second year of the COVID-19 pandemic, in Brazil. The data has been obtained through an online survey conducted to 158 consumers domiciled in the state of Paraná, in Brazil, and tabulated through simple analysis. The results show consumption preferences among locally produced food, highlighting the relevance of food acquisition channels based on proximity, especially in direct purchase from producers. This proximity relationship allows to obtain relevant information about how food is produced and processed, apart from the acknowledgement by people who had participated in such processes. It is concluded that the level of availability of information on the production method features, and relationships based on trust are key factors when choosing a marketing channels for food procurement.
Keywords: Consumption; animal proteins; food security; agri-food systems.